Novel targeting of the lepB gene using PCR with confronting two-pair primers for simultaneous detection of Mycobacterium tuberculosis complex and Mycobacterium bovis - Chayada Sitthidet Tharinjaroen (2018)
© 2016 The Authors. Tuberculosis (TB), caused by members of the Mycobacterium tuberculosis complex (MTC), is the leading cause of infectious disease-related mortality worldwide. The standard method for TB diagnosis usually requires long periods of mycobacteria cultivation, leading to delayed diagnosis, inefficient treatment and widespread occurrence of the disease. Therefore, a rapid method for the detection and differentiation of MTC from other mycobacteria is essential for disease diagnosis. Here, we describe the potential of using the type I signal peptidase (lepB) gene as a novel target for TB diagnosis, based on confronting two-pair primers PCR (PCRCTPP) that can detect MTC and simultaneously differentiate M. bovis. The limit of detection of the developed technique was equivalent to 12–120 bacilli. PCR-CTPP was highly specific to only MTC and M. bovis, and no cross-reaction was detected in 27 DNA of the non-tuberculous mycobacterial and bacterial strains tested. Thirty-nine blinded clinical isolates and 72 sputum samples were used to validate the PCR-CTPP in comparison with the standard mycobacterial culture method. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of PCR-CTPP were equal to 95, 100, 100 and 95%, respectively, when tested with clinical isolates. Furthermore, upon testing with the sputum samples, the sensitivity, specificity, PPV and NPV were observed to be 84, 76, 90 and 67%, respectively. Hence, this highly sensitive novel technique, which is rapid, easy to conduct and cost-effective, is a potential method for TB diagnosis and epidemiological studies, especially in resource-limited countries with a high TB burden.